Modeling for managing geographical data movement - Mohd. Shafry Mohd. Rahim; Ismail Mat Amin; Abdul Rashid Mohamed Shariff; Shattri Mansor; Ahmad Rodzi Mahmud; North Australian Remote Sensing and GIS Conference (2005 : Darwin, Australia) (Skudai : Universiti Teknologi Malaysia, 2005)
01